Microvascular Thrombosis, Fibrinolysis, Ischemic Injury and Death after Cerebral Thromboembolism Are Affected by Levels of Circulating α2-Antiplasmin - Reed, Guy L. (Arterioscler Thromb Vasc Biol, 2014)
OBJECTIVE: Ischemic stroke is primarily attributable to thrombotic vascular occlusion. Elevated α2-antiplasmin levels correlate with increased stroke risk, but whether α2-antiplasmin contributes to the pathogenesis of stroke is unknown. We examined how α2-antiplasmin affects thrombosis, ischemic brain injury and survival following experimental cerebral thromboembolism. APPROACH AND RESULTS: We evaluated the effects of α2-antiplasmin on stroke outcomes in mice with increased, normal or no circulating α2-antiplasmin, as well as in mice given an α2-antiplasmin-inactivating antibody. Higher α2-antiplasmin levels were correlated with greater ischemic brain injury (r(s)=0.88, p<0.001), brain swelling (r(s)=0.82, p<0.001) and reduced middle cerebral artery thrombus dissolution (r(s)=−0.93, p<0.001). In contrast, α2-antiplasmin deficiency enhanced thrombus dissolution, increased cerebral blood flow, reduced brain infarction and decreased brain swelling. By comparison to tissue plasminogen activator, α2-antiplasmin inactivation hours after thromboembolism still reduced brain infarction (p<0.001) and hemorrhage (p<0.05). Microvascular thrombosis, a process that enhances brain ischemia, was markedly reduced in α2-antiplasmin-deficient or α2-antiplasmininactivated mice compared with tissue plasminogen activator-treated mice or mice with increased α2-antiplasmin levels (all p<0.001) Matrix metalloproteinase-9 expression, which contributes to acute brain injury, was profoundly decreased in α2-antiplasmin-deficient or α2-antiplasmin-inactivated mice vs. tissue plasminogen activator-treated mice or mice with increased α2-antiplasmin levels (all p<0.001). Alpha-2-antiplasmin inactivation markedly reduced stroke mortality vs. tissue plasminogen activator (p<0.0001). CONCLUSIONS: Alpha-2-antiplasmin has profound, dose-related effects on ischemic brain injury, swelling, hemorrhage, and survival following cerebral thromboembolism. By comparison to tissue plasminogen activator, the protective effects of α2-antiplasmin deficiency or inactivation appear to be mediated through reductions in microvascular thrombosis and matrix metalloproteinase-9 expression.